2018
DOI: 10.3390/su10124808
|View full text |Cite
|
Sign up to set email alerts
|

Board Attributes and Corporate Social Responsibility Disclosure: A Meta-Analysis

Abstract: Many studies have examined the relationships between board attributes (board independence, CEO duality, board size, and women on boards) and corporate social responsibility disclosure (CSRD) as a means to improve a firm’s reputation. This research was performed in various international settings and uneven outcomes were obtained. We therefore meta-analyzed 88 studies to summarize scattered evidence and found that CEO duality had a significantly negative relationship with CSRD, while board independence, board si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 153 publications
(221 reference statements)
6
52
0
3
Order By: Relevance
“…But executives should consider both the costs and benefits of a large board as it costs more than a smaller board. Similarly, the presence of independent board members increases the decision-making quality, particularly in CSR and CSRD decision-making (Guerrero-Villegas et al, 2018;Zaid et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…But executives should consider both the costs and benefits of a large board as it costs more than a smaller board. Similarly, the presence of independent board members increases the decision-making quality, particularly in CSR and CSRD decision-making (Guerrero-Villegas et al, 2018;Zaid et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Bebbington, Russell, and Thomson () have pointed out that UN_SDGs are fundamental to upgrade social and environmental accounting research agenda. Schaltegger, Etxeberria, and Ortas () and Guerrero‐Villegas, Pérez‐Calero, Hurtado‐González, and Giráldez‐Puig () suggested that planetary boundaries and UN_SDGs should be essential parts for corporate sustainability accounting. Avrampou et al () provide a framework that is based on GRI performance indicators and scoring systems to compare and assess UN_SDGs through corporate sustainability reports.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…A proper corporate governance system is needed to decrease greenwashing and information overload (Ortas et al 2017) and to increase firm reputation. Especially, monitoring duties of non executive directors and the implementation of incentive-based compensation systems for top managers should strengthen substantial CSR management systems and avoid symbolic CSR activities (Guerrero-Villegas et al 2018).…”
Section: Introductionmentioning
confidence: 99%